Impaired histone deacetylases 5 and 6 expression mimics the effects of obesity and hypoxia on adipocyte function - Julien Bricambert; Dimitri Favre; Saška Brajkovic; Amélie Bonnefond; Raphael Boutry; Roberto Salvi; Valérie Plaisance; Mohamed Chikri; Giulia Chinetti-Gbaguidi; Bart Staels; Vittorio Giusti; Robert Caiazzo; et al. (Elsevier, 2016)
Objective: The goal of the study was to investigate the role of histone deacetylases (HDACs) in adipocyte function associated with obesity and hypoxia. Methods: Total proteins and RNA were prepared from human visceral adipose tissues (VAT) of human obese and normal weight subjects and from white adipose tissue (WAT) of C57Bl6-Rj mice fed a normal or high fat diet (HFD) for 16 weeks. HDAC activity was measured by colorimetric assay whereas the gene and protein expression were monitored by real-time PCR and by western blotting, respectively. RNA interference (RNAi) was used to silence the expression of genes in 3T3-L1 adipocytes. Results: Total HDAC activity was decreased in VAT and WAT from obese individuals and from mice fed a HFD, respectively. The HDAC activity reduction was associated with decreased HDAC5/Hdac5 and HDAC6/Hdac6 expression in human and mice adipocyte fraction. Similarly, hypoxia hampered total Hdac activity and reduced the expression of Hdac5 and Hdac6 in 3T3-L1 adipocytes. The decrease of both Hdac5 and Hdac6 by hypoxia was associated with altered expression of adipokines and of the inducible cAMP early repressor (Icer), a key repressor that is defective in human and mice obesity. Silencing of Icer in adipocytes reproduced the changes in adipokine levels under hypoxia and obesity, suggesting a causative effect. Finally, modeling the defect of the two Hdacs in adipocytes by RNAi or selective inhibitors mimicked the effects of hypoxia on the expression of Icer, leading to impairment of insulin-induced glucose uptake. Conclusion: Hdac5 and Hdac6 expression are required for the adequate expression of Icer and adipocyte function. Altered adipose expression of the two Hdacs in obesity by hypoxia may contribute to the development of metabolic abnormalities. Keywords: Histone deacetylases, Adipocytes, Adipokines, Obesity, Insulin resistance